Back Cover: Engineering of Nucleic Acids and Synthetic Cofactors as Holo Sensors for Probing Signaling Molecules in the Cellular Membrane Microenvironment (Angew. Chem. Int. Ed. 20/2019). Issue 20 (10th April 2019) - Feng, Guangfu; Luo, Xingyu; Lu, Xu; Xie, Shiyi; Deng, Lu; Kang, Wenyuan; He, Fang; Zhang, Jiaheng; Lei, Chunyang; Lin, Bin; Huang, Yan; Nie, Zhou; et al.
Abstract : A modular strategy for the construction of cell surface DNA sensors is presented by Z. Nie, C. Lei, and co‐workers in their Communication on page 6590 ff. By engineering DNA motifs and synthetic cofactors, they developed cell surface DNA sensors for ratiometric imaging of the extrusion of endogenous signaling molecules, including sulfur dioxide derivatives and nitric oxide.